2002
DOI: 10.1097/00007890-200210270-00003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ADAMTS13: a potential factor in the cause of thrombotic microangiopathy in a renal allograft recipient

Abstract: This is the first case to demonstrate a correlation between the presence of ADAMTS13 inhibitors and transplant-associated TMA. Autoimmune inhibitors of ADAMTS13 should be considered in patients with transplant-associated thrombotic microangiopathy. The role of calcineurin inhibitor in the formation of autoantibodies to ADAMTS13 remains to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…It is interesting that several groups have suggested that varying assays of ADAMTS13 activity and inhibitors are useful to predict clinical outcomes of patients who have TMA and are treated with plasma therapy (46,47). Nevertheless, it remains controversial whether a similar mechanism or clinical approach can be valid with patients who develop TMA after solid-organ transplantation, according to case reports that have evaluated this enzyme activity in blood samples of these patients (48,49). Unfavorable responses to PE in this report might be explained by different pathophysiology from deficiency in those factors, but these molecules were not examined in our study.…”
Section: Prognostic Analysesmentioning
confidence: 99%
“…It is interesting that several groups have suggested that varying assays of ADAMTS13 activity and inhibitors are useful to predict clinical outcomes of patients who have TMA and are treated with plasma therapy (46,47). Nevertheless, it remains controversial whether a similar mechanism or clinical approach can be valid with patients who develop TMA after solid-organ transplantation, according to case reports that have evaluated this enzyme activity in blood samples of these patients (48,49). Unfavorable responses to PE in this report might be explained by different pathophysiology from deficiency in those factors, but these molecules were not examined in our study.…”
Section: Prognostic Analysesmentioning
confidence: 99%
“…In rare cases, renal involvement is severe enough to cause endstage renal failure (1,(21)(22)(23)(24)(25). Those patients' clinical manifestations are difficult to distinguish from those of hemolytic uremic syndrome (HUS), a form of thrombotic microangiopathy characterized by predominant renal involvement, often with renal failure (1,20,26).…”
mentioning
confidence: 99%
“…Recently, the usefulness of serial assessment of these values was clearly shown in a patient with TMA after cadaveric renal transplantation. 15 In this patient, VWF-CP activity was undetectable at onset. PE effectively supplemented this protease, which was followed by complete resolution of disease and, subsequently, plasma levels sustained at normal values.…”
Section: Discussionmentioning
confidence: 66%
“…First, these drugs have been shown to cause dysregulation of endothelial cells, vasoconstriction of arterioles, an imbalance between prostacyclin and thromboxane A 2 production, and reduction of the generation of activated protein C, leading to extraordinary platelet aggregation. 13,15 Second, withdrawal of CsA or tacrolimus or switching from tacrolimus to CsA therapy or vice versa is recommended as initial management and often is successful, particularly in localized disease. Third, TMA in these settings usually occurs within 90 days of transplantation, suggesting that a relatively greater dose or blood concentration of calcineurin inhibitors may be crucial for disease development.…”
Section: Discussionmentioning
confidence: 99%